Comparison of blood loss in total knee replacement surgery with and without tranexamic acid: a prospective, time framed and observational analytical study - Mandal, Shaival; Chatterjee, B. D.; Kar, Abheek; Agarwal, Saumya (International Journal Of Community Medicine And Public Health, 2024)
Background: Total knee replacement is one of the common orthopaedic procedures performed worldwide. Blood transfusion is one of the major requirements in TKR procedure due to the amount of blood loss during and after the procedure. We carried out a prospective study to determine the efficacy of tranexamic acid in controlling blood loss during TKR procedure. Methods: Study was conducted at a tertiary care centre, involving cases operated by a single surgeon. Study included 140 patients undergoing primary TKR for advance degenerative disease of knee and were divided into two groups of 70 each, one group that received tranexamic acid before surgery and another group that did not receive tranexamic acid before surgery. Patient with allergy to the drug, hepato/renal dysfunction, DVT, abnormal PT and INR were not included. Tranexamic acid was given intravenously as well as intra-articular. Results: Pre-operative haemoglobin ranged from 10.2 gm% to 14.4 gm% in the group getting tranexamic acid and from 10% to 14 % in the group not getting tranexamic acid. Post operatively haemoglobin varied from 8.4 gm% to 12.8 gm% in Group 1 and from 7.8 gm% to 12 gm% in Group 2. Difference of mean post-operative Hb (p=0.0045) and PCV (p=0.0024) in two groups was statistically significant. Conclusions: We concluded that administration of tranexamic acid reduces the blood loss as well as need of blood transfusion in a patient undergoing total knee replacement.